Three new angel sharks (Chondrichthyes: Squatinidae) from the Indo-Australian region - Last, Peter R.; White, William T. (Zootaxa, 2008)
Four species of angel sharks (family Squatinidae) occur in temperate and subtropical Australian waters. Two of these, Squatina albipunctata sp. nov. and S. pseudocellata sp. nov., which occur mainly off subtropical eastern and western Australia respectively, are formally described and illustrated. The new species differ from temperate Australian species, S. australis and S. tergocellata, in morphometrics, meristics, squamation, and coloration. Another new angel shark, S. legnota sp. nov. from eastern Indonesia, is compared to these species. Unlike Australian Squatina, it has unfringed (rather than fringed) barbels on its nasal flap.